Evaluation of the Role of RTRW (Rencana Tata Ruang Wilayah) In Creating a Tourism Area Resilient To Landslide Disaster (Case Study: Petungkriyono District) - Ariani, Nofa Martina; Wijaya, Muhammad Indra Hadi; Puspasari, Deny Aditya; Susanti, Retno (Universitas Islam Sultan Agung Semarang, 2025)
Pekalongan Regency is an area with flat to steep topographic characteristics which makes this area prone to disasters ranging from floods, landslides, droughts, and tornadoes. This disaster vulnerability has an impact on the use of existing space, one of which is tourist areas. However, spatial planning for tourist areas in Pekalongan Regency does not appear to be fully regulated in the Regional Spatial Plan, even though most of the existing tourist areas are located in landslide-prone areas. This study will evaluate the role of RTRW in creating a landslide resilient tourist area in Petungkriyono District using the process of public policy implementation analysis method. The first stage is to analyze the level of landslide vulnerability using scoring and weighting techniques and then carry out an overlay analysis of the variables. used. The second stage is an evaluation analysis of the role of the RTRW carried out by looking at 3 (three) aspects including evaluation of the synchronization of Disaster Management (Landslide) Policies, evaluation of the Implementation of Zoning Arrangements and evaluation of Program Implementation in the Pekalongan Regency RTRW. Results The level of landslide vulnerability in tourist areas in Petungkriyono District ranges from high to very high. The Pekalongan Regency RTRW itself is a policy that focuses on spatial planning, so the evaluation in this case is the disaster management policy in the spatial RTRW. The results of the study state that the role of RTRW reached 86% (eighty six percent), which means that RTRW has played a very important role in creating a disaster-resilient tourist area in Petungkriyono District.